2020
DOI: 10.1177/1461444820977199
|View full text |Cite
|
Sign up to set email alerts
|

A snap of your true self: How self-presentation and temporal affordance influence self-concept on social media

Abstract: This study examined how self-presentation on social media influences the way people view themselves. It also examined whether that varies with sites using two temporal features: posts which have a short life (ephemeral) and those which live indefinitely (permanent). Drawing on both the notion of public commitment and self-symbolizing, our experiment provided a critical test of two rival theory-driven hypotheses—one suggesting a greater internalization of presented self on permanent rather than ephemeral social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…While our findings suggest only a small positive association of individual Stories (vs. Posts) with authenticity, such effects may accumulate. In the light of recent evidence showing that ephemeral social media did cue internalization of presented personality traits while permanent social media did not (S. Choi et al, 2020), even such slight effects may be meaningful to users. Still, whether selfperception effects as observed in our study develop into long-term changes of authenticity is a crucial question for future studies.…”
Section: Discussionmentioning
confidence: 84%
“…While our findings suggest only a small positive association of individual Stories (vs. Posts) with authenticity, such effects may accumulate. In the light of recent evidence showing that ephemeral social media did cue internalization of presented personality traits while permanent social media did not (S. Choi et al, 2020), even such slight effects may be meaningful to users. Still, whether selfperception effects as observed in our study develop into long-term changes of authenticity is a crucial question for future studies.…”
Section: Discussionmentioning
confidence: 84%
“…Likewise, we found no differences between Time Limit users and nonusers in terms of perceived stress and social anxiety. However, previous studies indicate the ephemerality of content gives users more control over their information ( Morlok et al, 2017 ) and in turn mitigates their concerns of self-presentation and impression management ( Bayer et al, 2016 ; Choi et al, 2020 ). One possible explanation is that we fail to capture participants’ actual psychological state.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we highlight the critical role of personal characteristics in ephemerality setting use, by systematically exploring how Time Limit users differ from nonusers regarding demographics, personality traits, psychological factors, and previous behavior patterns. Although several ephemerality studies indicated individual characteristics (e.g., life changes, maturity) would impact ephemeral content engagement in social media (Li et al, 2018;Luria and Foulds, 2021), as well as ephemerality feature could mitigate users' concerns (Bayer et al, 2016;Choi et al, 2020), these studies are fragment and most of them based on the qualitative method. Our work extends these prior studies as we empirically verified that individuals with higher level of posting frequency and privacy setting use would be more likely to employ the Time Limit setting.…”
Section: Implications and Limitations Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, self-presentations via ephemeral media may not afford or encourage the degree of editing and deliberation seen in persistent channels, rendering ephemeral presentations less persistent and impactful (cf. Choi et al, in press). While research that involves participants self-presenting on their own social media posts shows evidence of identity shift, research has yet to examine whether these participants decided to keep these posts on their timeline and if they did not, how deleting their post impacted the persistence of the identity shift observed earlier.…”
Section: Lessons Learned (But Not Always Published)mentioning
confidence: 99%